Designing responsive environments through User Experience research. (December 2016) - Hansen, Kai
Ubiquitous computing systems are changing the way retail environments are being designed. With increasing frequency, User Experience designers leveraging ubiquitous computing systems that observe and respond to user behaviors are assuming roles once held exclusively by architects. As these systems continue their growth, designers of environments will need to acknowledge the underlying role of experience designer and embrace User Experience methodologies. We will discuss how ubiquitous computing has been leveraged in our research, and our position on how these systems are impacting the design of retail environments, illustrated by several examples of User Experience research projects, informing the experience design of retail environments.